Development of CNS-type Primitive Neuroectodermal Tumor in Metastatic Testicular Mixed Germ Cell Tumor - Odisho, Anobel Y. (Urol Case Rep, 2016)
A 29-year-old man presenting with a retroperitoneal mass was found to have a testis lesion consistent with mixed germ cell tumor and the RPLND specimen showed teratoma with an area of central nervous system-type primitive neuroectodermal tumor (PNET) not present in the testis. Whether such primitive tumor components represent a de novo tumor component or represent progression from existing neuroepithelial teratomatous elements is unclear. Given the high likelihood of residual tumor and possibility of malignant transformation, post-chemotherapy RPLND remains vital in treating patients with testis cancer. PNET is chemo-resistant and lesions should be resected, without clear evidence for adjuvant chemotherapy.